LRIGs: A Prognostically Significant Family with Emerging Therapeutic Competence against Cancers - Malik, Uzma; Javed, Aneela (Current Cancer Drug Targets, 2017)
The human leucine-rich repeats and immunoglobulin like domains (LRIG) are evolutionary conserved family of single-pass transmembrane proteins. LRIG gene family includes three members, LRIG1 (formerly LIG1), LRIG2 and LRIG3, all of which are differentially expressed in human tissues and have long been proposed to be tumor suppressors. However, recently accumulated evidence on LRIG protein expression in human cancer appears to be inconsistent with this belief, as LRIG proteins have been found to be upregulated in certain tumors. Moreover, LRIG3 has been shown to act in an opposite manner to LRIG1 and LRIG1, in turn, has been shown to attenuate LRIG3 activity by its proteolytic degradation. These remarkable observations underline and reveal the previously unappreciated complexity of LRIG family dynamics. In the current review, the role of LRIG proteins in various human cancers is summarized and their differential regulation and expression is brought to light in order to understand how these proteins are involved in the genesis and progression of human cancers. Moreover, this is the first compilation that highlights the therapeutic potential of LRIG1 and suggests the same to be undertaken for LRIG2 and LRIG3. By virtue of their potential in prognosis of several cancer types, as well as their role as probable therapeutic proteins or in enhancing the receptiveness of the cancer cells to anti-tumor agents, it is strongly proposed that LRIG analysis should be undertaken and consequently be employed as a part of potential cancer treatment strategies.
Keywords: tumor suppressors